Exploring the Benefits of Pumpkin: The Harmony Between Hadith and Science - Daulay, Zhafirah Zahwa; Muhammad Nuh Siregar (Al-Bukhari : Jurnal Ilmu Hadis, 2025)
This study examines the benefits of pumpkin from two primary perspectives: Hadith and science. From the Hadith perspective, it explores how the Prophet Muhammad (peace be upon him) liked and encouraged the consumption of pumpkin, along with the wisdom behind his preference. From the scientific perspective, the study investigates the nutritional content and health benefits of pumpkin, such as maintaining heart health, enhancing immune function, and supporting the function of other organs. This research employs a qualitative method with a literature study approach, utilizing data sources from Hadith collections such as Sahih al-Bukhari and Sahih Muslim, as well as various scientific studies on the composition and benefits of pumpkin. The findings indicate that the Prophet Muhammad (peace be upon him) frequently consumed pumpkin, and scholars like Imam An-Nawawi and Ibn al-Qayyim elaborated on its health benefits, including aiding digestion, providing a cooling effect, and strengthening the immune system. From the scientific standpoint, pumpkin is proven to be rich in beta-carotene, vitamins A and C, fiber, and antioxidants that benefit eye health, skin, brain function, and the immune system. The harmony between Hadith and science in this regard demonstrates that the foods favored by the Prophet Muhammad (peace be upon him) hold not only spiritual value but also tangible health benefits.